2003
DOI: 10.1099/mic.0.26494-0
|View full text |Cite
|
Sign up to set email alerts
|

(De)regulation of key enzyme steps in the shikimate pathway and phenylalanine-specific pathway of the actinomycete Amycolatopsis methanolica

Abstract: Prephenate dehydratase (PDT), chorismate mutase (CM) and 3-deoxy-D-arabino-7-heptulosonate 7-phosphate (DAHP) synthase are key regulatory enzymes in aromatic amino acid biosynthesis in the actinomycete Amycolatopsis methanolica. Deregulated, feedback-control-resistant mutants were isolated by incubation of A. methanolica on glucose mineral agar containing the toxic analogue p-fluoro-DL-phenylalanine (pFPhe). Several of these mutants had completely lost PDT sensitivity to Phe inhibition and Tyr activation. Muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…In line with observations made for the type II enzyme from Amycolatopsis methanolica (47,48), it has been shown that MtuDAH7PS forms a complex with the M. tuberculosis chorismate mutase, resulting in significant activation of the latter enzyme (30). Phe and Tyr, the products of this branch of the pathway, inhibit this enhanced activity.…”
Section: Discussionsupporting
confidence: 52%
“…In line with observations made for the type II enzyme from Amycolatopsis methanolica (47,48), it has been shown that MtuDAH7PS forms a complex with the M. tuberculosis chorismate mutase, resulting in significant activation of the latter enzyme (30). Phe and Tyr, the products of this branch of the pathway, inhibit this enhanced activity.…”
Section: Discussionsupporting
confidence: 52%
“…Although these observations of the complex have been made from in vitro experiments, the in vivo importance of the interaction and activity boost has been recently exposed in an elegant directed evolution study where the activity of MtuCM and the activity boost afforded by MtuDAH7PS are reported by an E. coli selection system (16). Similarly, interactions between DAH7PS and CM are reported for pairings from a number of organisms including Corynebacterium glutamicum, Amycolaptoposis methanolica, and Brevibacterium flavum (27)(28)(29)(30). For these latter two organisms, enhanced CM catalytic activity was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Upstream from the phenylpropanoid pathway, the biosynthesis of aromatic compounds proceeds via the seven-step shikimate pathway to a branch point intermediate chorismate (Kloosterman et al, 2003). Chorismate subsequently is converted to three aromatic amino acids, tryptophan, tyrosine, and phenylalanine, as well as other aromatic compounds, via specific terminal pathways.…”
Section: Introductionmentioning
confidence: 99%